Antimicrobial susceptibilities of anaerobic bacteria isolated from female genital tract infections. - Hill, G B (1985)
Certain species or subspecies of anaerobic bacteria are isolated with higher frequency from female genital tract infections than from other anatomic sites. To gain susceptibility data more specific to the treatment of these infections, nine antimicrobial agents were tested by an agar dilution technique against 230 anaerobic bacteria isolated solely from obstetric and gynecological infections. These genital isolates were, in general, very susceptible to imipenem (most active, inhibiting all gram-negative rods at less than or equal to 1 microgram/ml), clindamycin (all isolates inhibited at less than or equal to 4 micrograms/ml), metronidazole (all gram-negative rods inhibited at less than or equal to 4 micrograms/ml), and chloramphenicol. Penicillin G had generally low activity against Bacteroides spp., not restricted to just the Bacteroides fragilis group, although it was very active against gram-positive species. Bacteroides bivius, a species uniquely common in female genital infections, was particularly resistant (90% MIC, 64 U/ml). Also, the Bacteroides melaninogenicus isolates were less susceptible than previously reported for isolates not exclusively from genital sites. Compared with moxalactam, cefotaxime, and cefoperazone, cefoxitin usually demonstrated equal or greater activity against most Bacteroides spp., with the exception of greater activity of moxalactam against B. fragilis (formerly subsp. fragilis). Resistance to moxalactam was observed among strains of Peptostreptococcus anaerobius, a common genital isolate. Overall, the activities of these four drugs were not as predictable as those observed for clindamycin, metronidazole, chloramphenicol, and imipenem.